O argumento de inclusão enquanto política de acesso à universidade pública - Griner, Almog (2012)
There are a great number of evidences showing that education is extremely important in many economic and social dimensions. In Brazil, education is a right guaranteed by the Federal Constitution; however, in the Brazilian legislation the right to the three stages of basic education: Kindergarten, Elementary and High School is better promoted and supported than the right to education at College level. According to educational census data (INEP, 2009), 78% of all enrolments in College education are in private schools, while the reverse is found in High School: 84% of all matriculations are in public schools, which shows a contradiction in the admission into the universities. The Brazilian scenario presents that public universities receive mostly students who performed better and were prepared in elementary and high school education in private schools, while private universities attend students who received their basic education in public schools, which are characterized as low quality. These facts have led researchers to raise the possible determinants of student performance on standardized tests, such as the Brazilian Vestibular exam, to guide the development of policies aimed at equal access to College education. Seeking inspiration in North American models of affirmative action policies, some Brazilian public universities have suggested rate policies to enable and facilitate the entry of "minorities" (blacks, pardos1, natives, people of low income and public school students) to free College education. At the Federal University of the state Rio Grande do Norte (UFRN), the first incentives for candidates from public schools emerged in 2006, being improved and widespread during the last 7 years. This study aimed to analyse and discuss the Argument of Inclution (AI) - the affirmative action policy that provides additional scoring for students from public schools. From an extensive database, the Ordinary Least Squares (OLS) technique was used as well as a Quantile Regression considering as control the variables of personal, socioeconomic and educational characteristics of the candidates from the Brazilian Vestibular exam 2010 of the Federal University of the state Rio Grande do Norte (UFRN). The results demonstrate the importance of this incentive system, besides the magnitude of other variables